Electroacupuncture stimulation using different frequencies (10 and 100 Hz) changes the energy metabolism in induced hyperglycemic rats - Figueiredo,Lanese Medeiros (2011)
PURPOSE: To investigate the effect of 10 and 100 Hz peripheral electro-estimulation (electroacupuncture, EAc) at Zusanli (ST-36) and Zhongwan (CV-12) acupoints on blood glucose and lactate levels and tissue (liver and kidney) concentrations of lactate in hyperglycemic induced anesthetized rats. METHODS: Thirty-six rats were randomly assigned to 3 groups (n=12): G1: basal (anesthesia: ketamine (90mg kg-1 body weight)+ xylazine (10mg/kg-1 body weight, i.p.); G2: anesthesia+EA10Hz EAc and G3: anesthesia+EA100Hz EAc). EAc stimulation was delivered for 30 min at 10 mA at selected acupoints. Blood and tissue (kidney, liver) samples were collected at the end of the EAc application (n=6, T30) and 30 minutes later (n=6, T60) for biochemical analysis. G1 samples were collected at the same timepoints. ANOVA followed by Tukey's Multiple Comparison Test was used for statistical analyses. RESULTS: Glycemia decreased significantly (p<0.001) in G2/G3 rats in all timepoints. Kidney and liver lactate concentrations decreased significantly (p>0.001) in G2/G3 rats at T-60 and at T30 timepoints in G2 compared with G1 rats. Lactacedemia decreased significantly at T30 timepoint in G2 compared with G1 rats. G1/G3 tissue lactate levels were not different. CONCLUSIONS: Electroacupuncture (10 Hz) applied to St-36 and CV-12 acupoints decreases glycemia and lactacedemia and liver and kidney lactate concentrations. We hypothesize that the decrease in lactate levels may be related to greater energy production due to enhanced lactate to pyruvate conversion. Higher frequency (100 Hz) failed to promote the same effect.